PERENCANAAN KONSENSUS ALIH FUNGSI LAHAN EKS PABRIK ES PT. SARIPETOJO MENJADI HOTEL SARIPETOJO SURAKARTA - , Okta Dwi Prabowo, Prof. Ir. Bakti Setiawan, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Plan of the Central Java Provincial Government represented by Perusahaan Daerah Citra Mandiri Jawa Tengah which will build a mall in a historic site âPabrik Es Saripetojoâ located in Kampung Jantirejo, Kelurahan Sondakan, Kecamatan Laweyan, Surakarta has created a disputed/ conflict. Such conflict has strarted in 2011 and finnaly finished in 2013. The research intends to find out the conflict cronology, the trigger of the conflict, the stakeholder involved, the solution process, type of the consensus planning and statisfaction level of stakeholders. The method applied in this research is descriptive-explorative. From the investigation in the field, the conflict has been triggered by the demolition of building which has been done by the developer âPT. Whira Taruna- without obeying the recomendation letter from the City Government of Surakarta